Human Resource Management Through Religious Programs for Student Character Development - Azizah, Luthfiana; Hikmawati, Hanifah; Muttaqin, Muttaqin (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study analyzes religious teachers' human resource management process at SMA Negeri 2 Ngawi in supporting student character development. The method used is descriptive qualitative research with data collection techniques through observation, interviews, and documentation. Researchers analyzed the data using the Miles and Huberman analysis model, including data collection, reduction, presentation, and conclusions or verification. The study results indicate that the recruitment process for religious teachers prioritizes religious aspects, participation in religious organizations, solidarity, and discipline. Teacher development is done directly through internal discussions, WhatsApp groups, sharing sessions, and shared perceptions. The religious team routinely performs monthly and semester evaluations to assess craftsmanship, discipline, and order improvements. Implementing this human resource management has succeeded in forming a compact team, establishing good communication, and creating a positive work environment, resulting in competent and disciplined religious teachers. This human resource management of religious teaching impacts improving the quality of religious programs implemented to develop student character so that students are more disciplined in worship, have an increased understanding of the fiqh of prayer, and are more responsible. In addition to realizing the success of the religious program, this can also provide insight to the community that public high schools also have the potential to improve religious character in students.